Gradient limits and intermediate landscapes in the dual metropoli of Medellin - Vélez Venegas, Claudia María; Rios Betancur, Luis Miguel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2020)
The urban border in the city of Medellín -metropolitan center of Aburrá valley- responds to occupation, development and expansion characteristics of many Latin American cities where suburban and periurban spaces are being built larger,  therefore, blurring the boundaries between the two. For this case study, those spaces are also presented as an interface space with adjacent metropolitan areas. The imaginary line that separated the urban-rural border, the municipal boundary and the metropolitan boundary only exists institutionally; its urban and landscape expression responds in a better way to the statement of this article with the concept of “gradient limits”, understood as the contrasting and inequal expression of the dual city, not only for its relation and distance to the center, but for being a spatial processes container that are installed in a differentiated and segregated way from the north towards the south of the city, and that can be visible through cartographies and other representations of this spatial transition. The relationship between the boundaries and the urbanization containment projects, that are shown, generate intermediate spaces as a result of tensions among those metropolization processes, with interface areas whose landscapes are in transition, some in deterioration and others in consolidation processes which, along with boundary areas, illustrate some of the contradictions and hybridization of the dual metropolis of Medellin.
Keywords: Metropolization; Expansion; Contrast; Periphery; Landscape